Exploring the role of nonlocal Coulomb interactions in perovskite transition metal oxides - Indukuru Ramesh Reddy; Chang-Jong Kang; Sooran Kim; Bongjae Kim (npj Computational Materials)
Abstract Employing the density functional theory incorporating on-site and inter-site Coulomb interactions (DFT + U + V), we have investigated the role of the nonlocal interactions on the electronic structures of the transition metal oxide perovskites. Using constrained random phase approximation calculations, we derived screened Coulomb interaction parameters and revealed a competition between localization and screening effects, which results in nonmonotonic behavior with d-orbital occupation. We highlight the significant role and nonlocality of inter-site Coulomb interactions, V, comparable in magnitude to the local interaction, U. Our DFT + U + V results exemplarily show the representative band renormalization, and deviations from ideal extended Hubbard models due to increased hybridization between transition metal d and oxygen p orbitals as occupation increases. We further demonstrate that the inclusion of the inter-site V is essential for accurately reproducing the experimental magnetic order in transition metal oxides.